Anti‐arrhythmic medications increase non‐cardiac mortality – A meta‐analysis of randomized control trials. Issue 3 (11th March 2016) - Pandya, Bhavi; Spagnola, Jonathan; Sheikh, Azfar; Karam, Boutros; Anugu, Viswajit Reddy; Khan, Asif; Lafferty, James; Kenigsberg, David; Kowalski, Marcin
Abstract: Introduction: Anti‐arrhythmic medications (AAMs) are known to increase cardiac mortality significantly due to their pro‐arrhythmic effects. However, the effect of AAMs on non‐cardiac mortality has not been evaluated. Methods: Trials published in English language journals from 1990 to 2015 were thoroughly retrieved by searching websites such as PubMed, Medline, Cochrane Library, and Google Scholar. Randomized controlled trials reporting non‐cardiac deaths as primary or secondary outcomes were used to compare AAMs to non‐arrhythmic therapy (AV nodal blocking agents, implantable cardiovascular defibrillation (ICD), or placebo). Information regarding the sample size, treatment type, baseline characteristics, and outcomes was obtained by using a standardized protocol. The fixed effect model was used to perform meta‐analysis, and results were expressed in terms of odds ratio (OR) with confidence interval (CI) of 95%, inter study heterogeneity was assessed using I 2 . Intention to treat principle was applied to extract data. Results: Total of 18, 728 patients were enrolled in 15 trials; 9359 patients received AAMs and 9369 received non‐arrhythmic therapy. AAMs were associated with an increased risk of non‐cardiac mortality (OR=1.30, [95% CI: 1.12, 1.50], p =0.0005, I 2 index=24%) and all‐cause mortality (OR=1.09, [95% CI: 1.01, 1.18], p =0.04, I 2 =54%) as compared to non‐arrhythmic therapy. There was no difference in the cardiac mortality (OR=1.01, [95% CI: 0.92, 1.11], p =0.82, I 2 =53%) or arrhythmic mortality (OR=1.00, [95% CI: 0.89, 1.13], p =0.94, I 2 =64%) between the two groups. Conclusion: AAMs are associated with an increased risk of non‐cardiac and all‐cause mortality. The effect of AAMs, especially amiodarone, on non‐cardiac mortality requires further evaluation.